2009
DOI: 10.3748/wjg.15.3931
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus dosage requirements in living donor liver transplant recipients with small-for-size grafts

et al.

Abstract: AIM:To investigate the tacrolimus dosage requirements and blood concentrations in adult-to-adult right lobe living donor liver transplantation (AALDLT) recipients with small-for-size (SFS) grafts. METHODS:During January 2007 and October 2008, a total of 54 cases of AALDLT with an observation period of 6 mo were enrolled in this study. The 54 patients were divided into two groups according to graftrecipient body weight ratio (GRBW): SFS grafts group (Group S, GRBW < 0.8%, n = 8) and non-SFS grafts group (Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…All the transplant patients were treated with tacrolimus and steroids for immuno suppression [25]. Steroids are known inducers of liver enzyme activities, although effect of tacrolimus on serum enzymes is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…All the transplant patients were treated with tacrolimus and steroids for immuno suppression [25]. Steroids are known inducers of liver enzyme activities, although effect of tacrolimus on serum enzymes is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The selection criteria for the donor and recipient as well as surgical techniques for both donor and recipient operations have been described in detail elsewhere [23] , [24] . A detail description of the immunosuppression regimen was described in previous investigation [25] . All patients were followed after surgery by our surgical team, with CT scans of the chest and abdomen every 3 months for the first 2 years and every 6 months thereafter.…”
Section: Methodsmentioning
confidence: 99%
“…Hence TAC clearance may change as the graft regenerates and changes in size after transplantation. 5,6 Several studies 5,6 have shown that the TAC dose requirement, which indirectly reflects TAC metabolism by the liver, increases gradually after LT as the new liver regenerates and liver function normalizes. The TAC concentration-dose ratio (CD ratio), estimated by dividing the TAC trough concentration (ng/mL) by the corresponding daily TAC dose (mg/day or mg/kg/day), has also been used to estimate TAC pharmacokinetics in several studies.…”
Section: Introductionmentioning
confidence: 99%